International(ization of) Higher Education at the Crossroads - de Wit, Hans; Hunter, Fiona (International Higher Education, 2014)
Where international higher education broadly analyses international developments in higher education at the system level, internationalization can be seen as a subcategory of this work, focusing more specifically on the international rationales, approaches, strategies, activities and outcomes of higher education at the regional, national and institutional level, and (where possible) in a comparative perspective. This special issue of International Higher Education seeks to highlight new and innovative dimensions in internationalization. It also gives space to examine developments in internationalization of higher education in regions and countries that are less known than English speaking countries and Western Europe. And it illustrates the increasing importance and diversity of internationalization’s conceptual understandings and lived experiences in modern international higher education. This annual special issue is a collaboration between the Center for International Higher Education at Boston College and the Centre for Higher Education Internationalisation at the Università Cattolica del Sacro Cuore in Milan.